In vitro tooth whitening effectiveness of whitening mouth rinses - Rodrigues, Ana Paula Morona (2020)
Regardless of the extensive availability of mouth rinses that claim to whiten teeth, evidence of achievement of such effect is still missing. Aim: Therefore, this study assessed in vitro the whitening effectiveness of whitening mouth rinses. Methods: Sixty intact bovine incisors were embedded in acrylic resin and had their buccal surface flattened and polished. Then, the specimens were randomly allocated to three conventional (Colgate Plax, Cepacol and Listerine Cool Mint) and three whitening mouth rinse groups (Colgate Luminous White, Cepacol Whitening and Listerine Whitening Extreme) (n=10). Following, the specimens were immersed twice a day in the mouth rinses for one minute for 28 days. In between each immersion period, the specimens remained in artificial saliva at 37oC. Color was measured at baseline, 7, 14, 21, and 28 days using a portable spectrophotometer (Easyshade, Vita Zahnfabrik, Germany) with a 6 mm of diameter probe. Color change was analyzed considering the parameters of ∆L*, ∆a*, ∆b* and, ultimately, ∆E*. The whitening efficacy of the mouth rinses was analyzed using the Whiteness Index for Dentistry (WID). Data of ∆s was analyzed using two-way ANOVA and Tukey’s test (α=0.05). Results: The type of mouth rinse affected significantly all the ∆ parameters (p<0.05). A non-whitening (conventional) mouth rinse produced the highest ΔE*, followed by the three whitening mouth rinses. The application time also affected ΔE* (p<0.05), with emphasis on the third week of treatment. Only the hydrogen peroxide-containing mouth rinse (Listerine Whitening Extreme) presented a whitening effect, with an increasing trend over time. Conclusion: Although the overall color change was not different when comparing conventional and whitening mouth rinses, the hydrogen peroxide-containing whitening mouth rinse produces an increasing whitening trend over time. Not every mouth rinse that claims to whiten teeth produces the desired effect.